PROGRAM SENI TARI DAERAH DALAM PEMBENTUKAN KARAKTER DI SEKOLAH DASAR NEGERI 3 PANGKALPINANG EVALUASI MODEL STAKE - Tri Agung Saputra; Pinkan Nurhaliza; Riska; Asyraf Suryadin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The regional dance arts program at SD Negeri 3 Pangkalpinang is held as a weekly extracurricular activity, with the main objective of developing expressive potential and internalizing character values in students in grades IV, V, and VI. However, observations indicate implementation constraints, particularly related to student absenteeism and significant limitations in program support facilities and infrastructure. This study aims to evaluate the effectiveness of the regional dance arts program in its contribution to student character formation, using the Stake Evaluation Model. This evaluation framework examines three crucial components: Antecedents (Initial Conditions) in this program are based on strong arguments regarding efforts to preserve cultural heritage and instill character values. Secondly, Transactions (Implementation Process) in the program implementation are carried out consistently through weekly sessions with demonstration methods and group practice. Thirdly, Outcomes (Achievements) in the program are proven to provide measurable positive contributions to strengthening student character, especially in the dimensions of discipline, responsibility, cooperation, and self-confidence. The research methodology involves comprehensive data collection through participant observation, in-depth interviews, and documentation analysis. The empirical evaluation results confirm that this program has successfully enriched aspects of student character development, particularly in strengthening discipline, responsibility, and collaboration skills. Therefore, this evaluation implies that the regional dance program plays a strategic role, not only as a mere extracurricular activity but also as an effective medium for preserving local culture and developing the holistic character of students at the elementary school level.